Unpacking the Pedagogical Mechanisms of Storytelling for Empathy Development in Early Childhood: A PRISMA-Based Systematic Review - Marvella Cynthia Dewi; Farida Kurniawati (FKIP Universitas Lampung, 2026)
This systematic literature review synthesizes empirical evidence on how different storytelling modalities, traditional oral storytelling, picture books, drama-based storytelling, digital storytelling, and multisensory approaches support empathy development in children aged 0-8 years. The review maps intervention designs, identifies targeted empathy dimensions, and examines underlying pedagogical mechanisms. Following PRISMA 2020 guidelines, a systematic search was conducted across four academic databases (Taylor & Francis Online, ProQuest, Scopus, and ScienceDirect). Eight peer-reviewed empirical studies met the inclusion criteria and were analyzed using descriptive and thematic synthesis. Storytelling interventions were generally associated with improvements in emotion recognition, perspective-taking, and prosocial tendencies, with stronger effects observed in interactive, moral, and culturally grounded storytelling. Digital and multisensory approaches showed potential to enhance emotional engagement, although evidence remains limited. Storytelling is a developmentally appropriate and promising approach for fostering empathy in early childhood. However, findings should be interpreted cautiously due to methodological heterogeneity. Further longitudinal and rigorously controlled research is needed. Keywords: storytelling, empathy, early childhood, social emotional learning.